Activity of lumacaftor is not conserved in zebrafish Cftr bearing the major cystic fibrosis‐causing mutation. Issue 10 (18th September 2019) - Laselva, Onofrio; Erwood, Steven; Du, Kai; Ivakine, Zhenya; Bear, Christine E.
Abstract: F508del‐cystic fibrosis transmembrane conductance regulator (CFTR) is the major mutant responsible for cystic fibrosis (CF). ORKAMBI ®, approved for patients bearing this mutant, contains lumacaftor (VX‐809) that partially corrects F508del‐CFTR's processing defect and ivacaftor (VX‐770) that potentiates its defective channel activity. Unfortunately, the clinical efficacy of ORKAMBI ® is modest, highlighting the need to understand how the small molecules work so that superior compounds can be developed. Because, human CFTR (hCFTR) and zebrafish Cftr (zCftr) are structurally conserved as determined in recent cryo‐EM structural models, we hypothesized that the consequences of the major mutation and small molecule modulators would be similar for the two species of protein. As expected, like the F508del mutation in hCFTR, the homologous mutation in zCftr (F507del) is misprocessed, yet not as severely as the human mutant and this defect was restored by low‐temperature (27°C) culture conditions. After rescue to the cell surface, F507del‐zCftr exhibited regulated channel activity that was potentiated by ivacaftor. Surprisingly, lumacaftor failed to rescue misprocessing of the F507del‐zCftr at either 37 or 27°C suggesting that future comparative studies with F508del‐hCFTR would provide insight into its structure: function relationships. Interestingly, the robust rescue of F508del‐zCftr at 27°C and availability of methods for in vivo screening in zebrafish present the opportunity to define the cellular pathways underlying rescue.